Analisis Penggunaan Film dalam Peningkatan Pemahaman Bahasa China Mahasiswa - Mariana, Mariana; Lin, Xuc (Bina Nusantara University, 2014)
Article explored to what extent students from the Chinese Department, Bina Nusantara University, were able to comprehend Mandarin language through â€œHome wih Kidsâ€ film. Qualitative method was applied by doing observation in class using prepared learning materials got from the film. There were 27 respondents coming from two classes. They were students from semester 1 who took Listening class. The writter also applied observation approach by distributing questionaires to students to know their comprehension of the film content. It can be concluded that students tend to be more enthusiastic in learning Chinese language by using film, and they are able to do the questions and retelling the plot of the film. This evidences prove that the influence of film gives more advantages to develop Chinese language proficiency of the Chinese department students, Bina Nusantara University.